Romania and the Eurasian Union. Plans, Predictions and Perspectives - Mircea-Cristian Ghenghea (CES Working Papers, 2016)
Following the events in Ukraine, Romania might represent one of the key points for the Eurasian perspectives that have circulated in the last years in Moscow. Through our text we intend to present and to highlight the main ideas and plans of Eurasian inspiration regarding Romania, as well as the interesting predictions made, in certain moments, by some representative characters for the Eurasian paradigm, like Aleksandr Dugin, for instance, who is its main ideologist and promoter. At the same time, one must not neglect the signals of discontent from Moscow about the need of dissipating the so-called sanitary cordon of the Western powers, in which the Baltic States, Poland, and Romania are included – another aspect bearing a particular importance for understanding certain gestures, attitudes and statements related to the role and the place of the Eurasian Union.
Keywords: F50; F53; F54; 330; Eurasian Union; Romania; Aleksandr Dugin